SMART GRID ENABLES DEREGULATED POWER SECTOR - ABHAS KUMAR SINGH (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper provides an overview of the role of Smart-grid in deregulated power sector. This includes the architecture and key feature of smart grid with Advantages, disadvantages and challenges to its adoption in the deregulated power sector. In the Deregulated power sector need of division between generation, transmission and distribution. Due to this market monopoly will be end and actual cost of power will be paid. For the calculation of actual data there is a need of real time data of consumption, generation and consumption. The accelerating installation of renewable electrical power generation has made the lot of requirement for a restructured electrical power system design. On the basis of specific configurations, particular rules and regulation it will then need to be improved. The Smart-grids can meet the price, efficient result, and environmental improvement; and the demand requirements for security, quality, reliability, and availability benefits of location generation, achieved by modern controls and operating. This will also useful for the reduction of CO2 emission. In the deregulated power sector all the calculation of cost depend on the real time data which can be obtained by smart meters and other components of smart grid.